2021
DOI: 10.3389/ijph.2021.1604219
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Wellbeing of 9–12-year-old Children in Northern Canada Before the COVID-19 Pandemic and After the First Lockdown

Abstract: Objectives: Children’s mental health and wellbeing declined during the first COVID-19 lockdown (Spring 2020), particularly among those from disadvantaged settings. We compared mental health and wellbeing of school-aged children observed pre-pandemic in 2018 and after the first lockdown was lifted and schools reopened in Fall 2020.Methods: In 2018, we surveyed 476 grade 4–6 students (9–12 years old) from 11 schools in socioeconomically disadvantaged communities in Northern Canada that participate in a school-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…To buffer negative mental health risks over time, promoting resilience in schools can foster positive coping skills, such as help-seeking, positive appraisal and thinking, and problem-solving [ 45 ]. During COVID-19, APPLE Schools programming focused on resilience-building strategies to maintain children’s psychological wellbeing [ 22 ], which is in line with strategies outlined in a recent School for Health in Europe Network Foundation guideline that focuses on implementation strategies based on the CSH (or health-promoting schools) approach during the COVID-19 pandemic [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To buffer negative mental health risks over time, promoting resilience in schools can foster positive coping skills, such as help-seeking, positive appraisal and thinking, and problem-solving [ 45 ]. During COVID-19, APPLE Schools programming focused on resilience-building strategies to maintain children’s psychological wellbeing [ 22 ], which is in line with strategies outlined in a recent School for Health in Europe Network Foundation guideline that focuses on implementation strategies based on the CSH (or health-promoting schools) approach during the COVID-19 pandemic [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…As part of fluctuating provincial restrictions on public gatherings and lockdowns, non-essential businesses and cultural venues were also closed, and extracurricular programmes for children were either suspended or operated in an online format, leaving school-aged children with few to no opportunities for social interaction or recreation. Nonetheless, APPLE Schools continued the active delivery of their programming during COVID-19 (including school closures and in-person learning), with a particular focus on maintaining school-aged children’s psychological wellbeing through mindfulness techniques and other strategies [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although the negative impact of the lifestyle changes, stay-at-home orders, lockdowns, and therefore social restrictions, was documented for various groups of the population, the adolescents might be especially vulnerable because of the developmental tasks and challenges [ 1 , 2 , 3 , 4 ]. Moreover, school-aged children might be experiencing additional specific strains because of prolonged school closure and distance education, and therefore reduced professional support, reduced social activities, and increased physical isolation from peers [ 3 , 5 , 6 , 7 , 8 , 9 ]. Thus, in adolescence, the additional pandemic challenges might have complicated every aspect of developmental strains and challenges posed by rapid physical and emotional growth itself, including increasing academic demands and expectations, changing social relationships with family and peers, and increasing exposure to online interactions [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…For children living in vulnerable environments, schools can act as a “protective layer” by providing mental health support and alternative social experience [ 7 , 28 ]. As schools play a critical role in children’s social development and are an integral part of the social support system in society [ 6 ], adolescents’ subjective evaluation of school as a social resource could be very important [ 22 ]. School social capital represents school students’ psychosocial resources such as social support, trust, reciprocity, social norms, social participation, integrity, and cohesion [ 29 ] available at school to facilitate educational outcomes and also to attain other life goals.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies show limited change, or a mixed pattern of results. An Italian study that followed a clinical sample of young adolescents longitudinally showed improvements in parent‐reported internalising and externalising symptoms during the pandemic (Di Giunta et al, 2021), while other North American longitudinal studies with children and young adolescents showed no change in symptoms compared with the prepandemic period (Dabravolskaj et al, 2021; Walters et al, 2021).…”
Section: Introductionmentioning
confidence: 99%